The protective effects of Mucuna pruriens seed extract against histopathological changes induced by Malayan cobra (Naja sputatrix) venom in rats - Fung, Shin Yee; Tan, N.H.; Liew, S.H.; Sim, S.M.; Aguiyi, J.C. (Malaysian Society of Parasitology and Tropical Medicine, 2009)
Seed of Mucuna pruriens (Velvet beans) has been prescribed by traditional medicine practitioners in Nigeria as a prophylactic oral antisnake remedy. In the present studies, we investigated the protective effects of M. pruriens seed extract (MPE) against histopathological changes induced by intravenous injection of Naja sputatrix (Malayan cobra) venom in rats pretreated with the seed extract. Examination by light microscope revealed that the venom induced histopathological changes in heart and blood vessels in liver, but no effect on brain, lung, kidney and spleen. The induced changes were prevented by pretreatment of the rats with MPE. Our results suggest that MPE pretreatment protects rat heart and liver blood vessels against cobra venom-induced damages.